39.4k views
20 votes
Need help solving this problem

Need help solving this problem-example-1
User Sthg
by
4.7k points

1 Answer

5 votes

Answer:

Explanation:

q is TFTF

~q use negation, not q so is the opposite of q : FTFT

p↔~q use biconditional ,and will be True only is both statements are T or both are F

p values are TTFF ↔~q values are FTFT : FTTF

(p↔~q )∧~q use conjunction, that is True only if both statements are T

(p↔~q ) values are FTTF ∧~q values are FTFT : FTFF

(p↔~q )∧~q → p use a conditional statement, where only True False will give a F

(p↔~q )∧~q values are FTFF → p values are TTFF : TTTT

Need help solving this problem-example-1
User DynamicallyCRM
by
4.7k points